2020
DOI: 10.1088/1755-1315/418/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Population of oil palm pollinator insect (Elaeidobius kamerunicus faust.) at PTP Nusantara VIII Cisalak Baru, Rangkasbitung-Banten

Abstract: The role of Elaeidobius kamerunicus in oil palm plantations in recent times is questioned related to the decline in oil palm productivity. The research aim is to study the E. kamerunicus beetle population and the factors that influence it. The study was carried out in the oil palm plantation PTP Nusantara VIII Cisalak Baru, Rangkasbitung-Banten. The beetle population were calculated on 3 spikelets at the base, middle, and end of an anthesis flower bunch of oil palm plant samples aged 13 and 5 years using purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…E. kamerunicus spent most of its life cycle in the male inflorescences of oil palms [ 17 , 27 , 39 ]. Its reproduction rate is strongly associated with the availability of male inflorescences apart from feeding on the anther filaments [ 39 , 40 ]. Being a holometabolous insect, this weevil species develops through different stages: egg, larva, pupa, and imago [ 41 , 42 ].…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…E. kamerunicus spent most of its life cycle in the male inflorescences of oil palms [ 17 , 27 , 39 ]. Its reproduction rate is strongly associated with the availability of male inflorescences apart from feeding on the anther filaments [ 39 , 40 ]. Being a holometabolous insect, this weevil species develops through different stages: egg, larva, pupa, and imago [ 41 , 42 ].…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
“…Additionally, T. hawaiiensis is better adapted to the dry season and maintains optimal pollination services during this time [ 34 ]. While climatic factors impact pollination activity, E. kamerunicus is less affected compared to other insect pollinators, allowing it to maintain pollination services even during the wet season [ 27 , 40 ].…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, host-specificity testing found that the species was unable to complete its life cycle on any plant species in the country other than the oil palm; thus, it was deemed safe to be introduced [ 8 ]. Elaeidobius kamerunicus is holometabolous, completing its development on post anthesis oil palm male inflorescence [ 9 , 10 ]. Adult female oviposit eggs on the male oil palm inflorescence, and the larva emerge and undergo perfect metamorphosis.…”
Section: Introductionmentioning
confidence: 99%